Food related routines and energy policy: A focus group study examining potential for change in the United Kingdom. (May 2018) - Hoolohan, Claire; McLachlan, Carly; Mander, Sarah
Abstract: This paper explores the interlinkages between energy demand and food-related routines, to understand how routines that benefit energy demand management throughout the food system might be encouraged. Building on existing social science research, focus group data are used to examine the routines of people in three work-life situations; working parents, city dwellers, and empty nesters. A critical space in which to examine aspects of everyday life that entrench everyday routines is created by examining peoples' feelings about their present routines and their aspirations for change. The resulting discussions illustrate the role of social and temporal commitments in shaping food routines, and how the different modes of provision, meals and methods of cooking used to navigate these commitments influence what is purchased and eaten. These aspects of everyday life therefore contribute to reinforcing and replicating patterns of energy use throughout the food system. The following discussions develop these initial findings to explore how interventions might support individual experimentation with alternative shopping, cooking and eating practices, and in so doing influence the ongoing evolution of food-related routines to the benefit of energy demand management.